Penegakan Hukum Terhadap Penyedia Narkotika Magic Mushroom : Studi Kasus Putusan Nomor 758 / Pid.Sus / 2016 / PN. Dps) - Aldi Pramana; Syafruddin Kalo; Muhammad Hamdan; Muhammad Ekaputra (USU LAW JOURNAL, 2019)
Abstract. Narcotics are one type of hazardous substance for humans. In its development narcotics are found which are sometimes unknown to the public. Like Magic mushroom, a type of fungus that grows in animal waste.Mushroom Magic Mushroom is not a type of fungus that we usually eat but mushrooms that can cause hallucinations and if consumed will make the user always happy or euphoric and can experience excessive sadness. In detail Magic Mushroom has the Latin name Panaeoluscyanescens also called cow dung mushroom or wong necklace or sacred mushroom, which grows on top of livestock manure in the form of toadstools that have flat oval spores and sporogonium tapered tips and white and will turn to ash gray to dark brown. In this case the author is interested in researching how the legal arrangements regarding narcotics Magic Mushroom and how the court considers in deciding the Magic Mushroom Narcotics Provider. This research method is legal research (legal research), to find the truth of coherence. This type of research is normative research. with a literature study of primary, secondary and tertiary legal materials. Based on the research that legal mushroom narcotics law regulation is found in the Law of the Republic of Indonesia Number 8 of 1996 concerning Ratification of Convention On Psychotropic Substances 1971 (Psychotropic Convention 1971). And Law Number 35 of 2009 concerning Narcotics. In addition, consideration of the court in deciding the Magic Mushroom Narcotics Provider or mushroom PanaeolucsyAnescens as Narcotics in Decision Number 758 / Pid.Sus / 2016 / PN Dps On behalf of the Defendant: KetutWinartha Researcher Disagrees with the Panel of Judges this is due to lack of legal certainty regarding magic The mushroom in the annex of Law No.35 of 2009 concerning Narcotics and judges also decides in doubt that the principle of dubio pro reo should apply rather than multi-interpretation.   Keywords: drugs, magic mushroom, psychotropic